Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi IPAS Cerita tentang Daerahku di Kelas IV SDN Model Mataram - Yuyun Lestari; Khairun Nisa; Dwi Supriatin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the improvement in students’ critical thinking skills in the IPAS topic Cerita Tentang Daerahku through the implementation of the Problem Based Learning model in Grade IV at SDN Model Mataram. This research employed Classroom Action Research using the Kurt Lewin model. The research subjects were 21 fourth-grade students of SDN Model Mataram. Data collection techniques included tests, observations, and documentation. The results indicate that the implementation of the Problem Based Learning model effectively improved students’ critical thinking skills in the Cerita Tentang Daerahku topic. This improvement is reflected in the gradual increase in students’ learning outcomes across each cycle. The average critical thinking score in Cycle II reached 81.19, while in Cycle I it was 54.28, showing an increase of 26.91 points. The post-test results also demonstrated a relatively significant difference compared to the pre-test results. These findings indicate that the Problem Based Learning model is highly effective in enhancing students’ critical thinking skills in the Cerita Tentang Daerahku topic for Grade IV students at SDN Model Mataram.